2021
DOI: 10.1016/j.scitotenv.2020.142314
|View full text |Cite
|
Sign up to set email alerts
|

Microbial abundance and community composition in biofilms on in-pipe sensors in a drinking water distribution system

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…Similarly, the family Nitrosomonadaceae showed higher relative abundance under high monochloramine conditions on Campus B (7.30% for YSB and 9.56% for MPB) when compared to Campus A (0.02% for YSB_A and 2.40% for MPB_A). Nitrosomonadaceae (betaproteobacteria class) are ammonia oxidizers that play an important role in drinking water networks (Cruz et al 2020, Kitajima et al 2020, Pérez et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the family Nitrosomonadaceae showed higher relative abundance under high monochloramine conditions on Campus B (7.30% for YSB and 9.56% for MPB) when compared to Campus A (0.02% for YSB_A and 2.40% for MPB_A). Nitrosomonadaceae (betaproteobacteria class) are ammonia oxidizers that play an important role in drinking water networks (Cruz et al 2020, Kitajima et al 2020, Pérez et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, biofilm formation has been associated with the detection of a deposit on a surface using differential turbidity measurement (DTM) between the clean and colonized probe (Flemming et al 1998). The online WaterWise system was initially developed to detect leakages but has also enabled additional real-time monitoring of water quality parameters, including pH, ORP, temperature, conductivity and turbidity, for the whole DWDS in Singapore (Allen et al 2013, Kitajima et al 2020, PUB 2016). Kitajima et al (2020) suggested that water age and monochloramine drive the community of both biofilm and bulk water samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of functional gene primers to quantify nitrifiers using ddPCR was necessary to overcome the limitations of qPCR in terms of a higher detection limit and sensitivity to amplification. In the survey of bulk water and biofilm communities in the local DWDS network with in-pipe sensors, a discrepancy was observed between the quantitation of total Archaea with ddPCR and the detection of archaeal amoA with qPCR (Kitajima, M. et al 2020).…”
Section: Designing Nitrifier Primers For Ddpcr and Qpcr Applicationsmentioning
confidence: 99%
“…In that study, an archaeal 16S rRNA gene primer was used for ddPCR quantification (Yu, Y. et al 2005, Kitajima, M. et al 2020, while the full-length archaeal amoA primer was used for qPCR quantification (Francis, C.A. et al 2005, Kitajima, M. et al 2020.…”
Section: Designing Nitrifier Primers For Ddpcr and Qpcr Applicationsmentioning
confidence: 99%